Microbes and biotechnology for the advancement of health, food production and agriculture : [text proceedings] - Malaysian Society for Microbiology Symposium (23rd : 2000 : Aseania Resort Langkawi); Malaysian Society for Microbiology; Universiti Putra Malaysia (Langkawi : MSM, 2000)
42